Alzheimer’s Dementia due to Suspected CTE from Subconcussive Head Impact - Shauna H. Yuan; Sonya G. Wang (Case Reports in Neurological Medicine)
Chronic traumatic encephalopathy (CTE) has been receiving increasing attention due to press coverage of professional football players. The devastating sequelae of CTE compel us to aim for early diagnosis and treatment. However, by current standards, CTE is challenging to diagnose. Clear clinical diagnostic criteria for CTE have not been established. Only recently, pathological diagnostic criteria have been recognized, but postmortem diagnosis is too late. Reliable biomarkers are not available. By imaging criteria, cavum septum pellucidum has been the only consistent identifiable MRI finding. Because of the imprecise nature of diagnosis based on clinical suspicion, physicians must become cognizant of the broad spectrum of presentations of CTE. With this awareness, appropriate workup can be initiated. CTE can present with early symptoms of emotional changes or late symptoms with memory decline and dementia. Here we present an unusual case of a patient with Alzheimer’s disease secondary to suspected CTE that stems from subconcussive head impacts presenting with severe memory and MRI changes. Clinicians should be aware of this presentation and consider CTE in their differential diagnoses while undergoing workup of memory disorders.